Real world safety of CT-P10 (anti-CD 20 monoclonal antibodies biosimilar) in rheumatic and autoimmune diseases - Katchamart W. (2023)
Background: Rituximab (RTX), anti-CD 20 monoclonal antibodies, has been approved for many rheumatic and autoimmune diseases, the use of RTX is still limited due to financial constrain. Biosimilar RTX may increase access by offering patients a more affordable option, lead to improved patient outcomes. However, real-world data related to its immediate and short-term safety is scarce. This study aimed to evaluate the real-world immediate and short-term safety profiles of CT-P10, a biosimilar of Rituximab, in patients with rheumatic and autoimmune diseases. Methods: This prospective study included patients diagnosed with rheumatic or autoimmune diseases, aged ≥ 18 years, who were treated with biosimilar RTX at Siriraj or Ramathibodi Hospital during February 2019 to May 2019. Patients were followed up through 6 months after the infusions. Results: Of the 74 patients, with 124 infusions, 84% were females with mean age (SD) of 49.4 (15.7) years. The most common rheumatic and autoimmune disease included in this study was systemic lupus erythematosus (26%). All immediate adverse events (AEs) (15 out of 124 infusions) were mild requiring only symptomatic and supportive treatment. Short-term AEs included infection (N = 35), hematologic abnormalities (N = 33), chylous ascites (N = 1), and others (N = 10). Two deaths were related to serious bacterial and viral infection. Hematologic AEs comprised anemia (N = 5), neutropenia (N = 10), lymphopenia (N = 15), and thrombocytopenia (N = 3). Conclusion: In this real-world study, biosimilar RTX (CT-P10) has favorable immediate and short-term safety profiles. However, further studies with large sample size and long-term follow-up in real-world practice are still required to confirm the result.